Machinability of al-11si-2cu cast alloy modified by bismuth, strontium or antimony / Mohsen Marani Barzani - Mohsen Marani, Barzani (2015)

(untitled)
Aluminum-silicon alloys are notable materials owing to their fine thermal conductivity, low expansion coefficient and good corrosion that can be utilized in the fields of automotive industry such as cylinder blocks, cylinder heads, brake discs, pistons and valve lifters. Modification of melt treatment in Al-Si cast alloys leads to a change in the morphology of eutectic silicon, resulting in mechanical properties enhancement. This enhancement affects the machinability of Al-Si alloys (i.e. cutting forces, surface roughness, tool wear and chip morphology). Near-eutectic alloys are the most difficult to machine of the various Al-Si alloys because, the silicon phase present is almost ten times harder than the aluminum base alloy, which rapidly increases tool wear, these difficulties have thus created the need for a more in-depth understanding of the effects of microstructure on the machinability of these alloys. Compared with other techniques, melt treatment with addition of inoculation agents known as modifier or refiner elements is more practical method due to low production cost and suitability for general engineering applications. Despite previous studies on microstructure of Al-Si alloys, there is lack of information on the effect of Bi, Sb and Sr additions that extensively address the influence of these elements on machinability characteristics of Al-11Si-2Cu cast alloy when dry turning. Understanding the machinability of these alloys is imperative when it is necessary to fabricate some industrial products which are produced by casting process. Therefore, the aim of this research was to investigate the machinability characteristics of Al-11 Si2Cu alloy containing bismuth, antimony and strontium when dry turning using coated carbide inserts. The influence of additional elements on mechanical properties was also investigated by conducting hardness, tensile and impact tests. iv Machining of workpieces was completed using a CNC turning machine (ALPHA 1350S) with an 8.3 kW power drive. Various cutting speeds of 70, 130 and 250 m/min and various feed rates of 0.05, 0.1 and 0.15 mm/rev were employed. Pure Bi shots, pure Sb and Sr granules at concentrations of 1wt.%, 0.5.% and 0.04.% were selected based on the optimum concentration for each additive as determined by microscopic inspection. The results indicated that surface roughness and cutting force decreased with increasing cutting speed from 70 m/min to 250 m/min, additionally, change of silicon morphology from flake-like to lamellar structure affects the machinability parameters. It was found that the Bi-containing workpiece had the best surface roughness value and lowest cutting force due to formation of pure Bi which acts as lubricant on the machined surface, while Sr-containing workpiece produced the highest cutting force and highest surface roughness value. Bi-containing alloy produced segmentation chips (C-shape) in comparison with other alloy elements, which led to separation of chip segments at outer (free) surface. Sr and Sb-containing alloys increased ductility of alloys which led to the production of massive BUE during machining process, resulting in increased flank wear. Impact test shows that absorbed energy value for the base alloy was around 1.15J, whereas it increased to 2.2J for Sr treated alloy.